Variations in health literacy and influential factors affecting the categories of social support among rural patients with diabetes mellitus - Zhang, Xin; Zhang, Yan-Ping; Zeng, Lin; Li, Xiang; Han, Jia-Xia; Fu, Gui-Fen; Bai, Chao-Qun; Lei, Xiao-Xue (Frontiers in Public Health, 2024)
Objective The aim of this study is to explore the inherent classification of social support among individuals residing in rural areas of China. Additionally, we aim to examine the attributes and variations in health literacy scores among patients with diabetes mellitus (DM) within diverse social support categories. Design Cross-sectional study. Methods Employing the multi-stage stratified sampling technique, we enrolled 2,178 patients diagnosed with DM residing in the rural regions of Guangxi Province. We utilized the General Information Questionnaire, Social Support Rating Scale (SSRS), and Functional, Communicative and Critical Health Literacy Instrument. Results The rural patients with DM were categorized into four distinct groups based on the types and levels of their underlying social support. These groups included a low-level social support utilization group (43%), a low-level objective social support group (17%), a moderate-level social support group (20%), and a high-level social support and high-level utilization group (20%). Statistical analysis revealed significant differences among the four groups in terms of age, disease duration, and blood sugar control level (p < 0.05). Furthermore, health literacy scores and scores across various dimensions for rural patients with DM demonstrated variability in accordance with latent profiles of social support, with statistically significant differences observed (p < 0.05). A positive correlation was identified between the level of social support and all dimensions of health literacy among rural patients with DM (p < 0.05). Conclusion The social support available to individuals with DM in rural settings can be categorized into four distinct types, and its manifestation is influenced by demographic factors. The health literacy of rural patients with DM is intricately linked to the extent of social support they receive. For enhanced outcomes, interventions targeted at enhancing health literacy and quality of life among rural patients with DM should be tailored to address the heterogeneity observed in latent profiles of social support.